Ethics, EBM, and hospital management - Biller-Andorno, N. (Journal of medical ethics, 2004)
Matters of hospital management do not figure prominently on the medical ethics agenda. However, management decisions that have to be taken in the area of hospital care are in fact riddled with ethical questions and do have significant impact on patients, staff members, and the community being served. In this decision making process evidence based medicine (EBM) plays an increasingly important role as a tool for rationalising as well as rationing health care resources. In this article, ethical issues of hospital management and the role of EBM will be explored, with particular reference to disease management programs, diagnosis related groups, and clinical pathways as recent developments in the German health care system.